The degree of includes history book for the first literary secondary grade with Critical thinking skills in light of the list of national standards (Journal of Hama University, 2025)
The aim of the current research is to reveal the degree of includes history book for the first literary secondary grade Critical thinking skills in light of the list of national standards. The researcher followed the descriptive analytical approach, and extract from of national standards a list of critical thinking skills designated for the first literary secondary grade, It consisted of the critical thinking skill  as its main skill followed by (15) indicators indicating this skill, and the research sample included all the contents this book.the reached results showed: Most  of Critical thinking skill indicators stipulated in the national standards are included in the content history book for the first literary secondary grade to a weak degree, and in varying percentages among them, it ranged between (1.10% - 16.57%). In addition  indicator of extracting facts from historical texts, it was mentioned in the book's content to moderate  degree and percentages (38.12%). The absence of a logical and gradation in including  indicators of the critical thinking skill  that were included in the book's content,  as their repetitions ranged between (0-69) repetition. Not including some indicators of the critical thinking skill  in the book's content completely, thus it becomes clear that , the content of national standards a list for critical thinking skills specified for the history subject  for the first literary secondary grade was not fully adhered to. Most of the critical thinking skill indicators analyzed in the book were presented in the form of an explanation and question with percentage of (84.52)  the total forms of  occurrence of this skill  in the book, it was rarely mentioned in the form of activities and form, as their  ratios together (16.48%) only.Based on this, the researcher suggested: Reformulating the content of the history book for the first literary secondary grade so that  national standards  are taken into account in including  critical thinking skills in the book according to an organized and clear scientific methodology. And conducting other studies that address critical thinking skills in the history books in light of national standards for different educational levels. and degree to which students in the first literary secondary grade acquire the critical thinking skills specified in the national standards and  revealed by the analysis process and difficulties prevent this.
Keywords: History, critical thinking, critical thinking skills.